Penerapan Metode Slope One dan K-Nearest Neighbor Untuk Menentukan Rekomendasi Tempat Makan di Bali Berbasis Android - Lucy Rosalind; Leo Willyanto Santoso; Lily Puspa Dewi (Jurnal Infra, 2021)
Restaurants are an alternative if there is no food at home or whenyou are traveling somewhere. Bali is one of the popular tourismcities because of the many tourists. The number of restaurantsmakes users confused to choose a restaurant that suits theirneeds. This recommendation application is made to help users inchoosing the restaurant that suits their needs easily.The initial step taken is the scraping process, after the scrapingprocess the next step is looking for restaurants that do not putprices which will later be calculated with the price prediction withthe Slope One algorithm after the data entered into the database.The recommendation calculation is done on the backend. When onAndroid, it only needs to make API calls.Based on the results of the tests that have been carried out, theprogram has succeeded in collecting data, managing, anddisplaying restaurant data. The price prediction process with theSlope One algorithm has very good results. For the process ofscraping the data to be retrieved as the original data. The KNearest Neighbor calculation process was successfully carriedout and has sufficient accuracy with K of 35, has an accuracy of59%, and contains data of 7,890 restaurants.